Rhetorical Strategies of the Introductory Chapter of Doctoral Theses in Education - Difabio de Anglat, Hilda; Alvarez, Guadalupe (Íkala, Revista de Lenguaje y Cultura, 2019)
This paper presents an analysis of the introductory sections of 26 Ph. D. theses in Education written in Spanish. It intends to make an approximation to their rhetorical strategies (movements and steps), in order to establish whether the texts show a common structure, whether the structure reproduces the model that the work seeks to contrast and which are the most frequent steps. The analysis follows the model of Jara Solar (2013), completed with some steps of Bunton (2002), those who extend the Swalesian approach (1990, 2004), given that they present introduction chapter as a section of three rhetorical movements (Establishing the Territory/Establishing the Niche/Occupying the Niche-Presenting the work) each of which includes steps, but they add new ones to those that Swales identified. Results show that the academic conventions appear in move I and move III, even though they may be missing some required steps. On the con-trary, 35% of texts or does not include the second movement or occupies it in a very synthetic way. Finally, cyclical configurations and embedding gener-ate more complex organizations. Brief practical implications for teaching are discussed.